Predictors of Parental Vaccine Hesitancy/Refusal towards COVID-19 Vaccines in North Cyprus - Varoğlu, Serpil (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2024)
This study aimed to investigate whether certain factors such as conspiracy, rumination, and parenting styles could predict parental vaccine hesitancy/refusal toward COVID19 vaccines. The COVID-19 virus has been a massive health threat worldwide and has resulted in vast number of human lives. To prevent and lessen the impact of the virus, vaccines have been implemented. These vaccines are now also available for children however, parental refusal and hesitancy to vaccines were observed all over the world. An online survey was conducted to investigate parental COVID–19 vaccine hesitancy/refusal on a sample of 200 parents from North Cyprus. The online questionnaire gathered information on demographic information, parenting disciplinary styles, trust to health care professionals and government, conspiracy, and ruminative thinking. The variables investigated were found to lead to vaccine hesitancy/refusal for children and for themselves. Conspiracy thinking was found to result in parental vaccine hesitancy/refusal whereas ruminative thinking was found to reduce hesitancy towards vaccines. Decreased levels of trust in health authorities and government were also a good predictor of vaccine hesitancy/refusal. Poor supervision in parenting was also found to be negatively correlated with vaccine hesitancy/refusal. Reviewing these predictor variables for vaccine hesitancy/refusal can be a good indicator for vaccination strategies. It can also offer a likely solution to prevent parental vaccine hesitancy/refusal currently and in the future.

ÖZ: Bu çalışma, komplo, ruminasyon ve ebeveynlik stilleri gibi belirli faktörlerin ebeveynlerin COVID-19 aşılarına karşı aşı tereddüdünü tahmin edip edemeyeceğini araştırmayı amaçladı. COVID-19 virüsü dünya çapında büyük bir sağlık tehdidi olmuştur ve çok sayıda insanın hayatına neden olmuştur. Virüsün etkisini önlemek ve azaltmak için aşılar uygulanmıştır. Bu aşılar artık çocuklar için de mevcuttur, ancak tüm dünyada ebeveynlerin aşıları reddetmesi ve tereddüt etmesi gözlemlenmiştir. Kuzey Kıbrıs'tan 200 ebeveynden oluşan bir örneklem üzerinde ebeveynlerin COVID19 aşısı tereddütlerini araştırmak için çevrimiçi bir anket yapılmıştır. Çevrimiçi anket aracılığıyla, demografik bilgiler, ebeveynlik disiplin stilleri, sağlık uzmanlarına ve hükümete güven, komplo ve ruminatif düşünme hakkında bilgi toplanmıştır. İncelenen değişkenlerin çocuklar ve kendileri için aşı tereddüdüne yol açtığı tespit edilmiştir. Komplo düşüncesinin ebeveynlerde aşı tereddüttü ile sonuçlandığı, ruminatif düşüncenin ise aşılara karşı tereddüttü azalttığı bulunmuştur. Sağlık otoritelerine ve hükümete olan güven düzeylerinin düşük olması da aşı tereddüdünün önemli bir göstergesi olmuştur. Ebeveynlikte zayıf denetimin de aşı tereddüttü ile negatif ilişkili olduğu bulunmuştur.
Master of Science in General Psychology. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Psychology, 2024. Supervisor: Prof. Dr. Fatih Bayraktar.
Keywords: Psychology Department; General Psychology; Parents--Psychology--Vaccine, Covid 19--Cyprus (Turkish Republic of Northern Cyprus, 1983-); COVID-19 (Disease)--Vaccination--Vaccine Hesitancy / Refusal--Cyprus (Turkish Republic of Northern Cyprus, 1983-); COVID-19 (Disease)--ychological aspects; Vaccines--Social Aspects--Psychology; COVID-19 Pandemic, 2020--Health services accessibility; Vaccination of children--Parents, Psyschology--Vaccination Refusal; Vaccine Hesitancy/refusal, COVID-19, Conspiracy Thought, Ruminative Thinking, Parenting